2023
DOI: 10.3390/ani13040703
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Assessment of the Pulmonary Vein to Pulmonary Artery Ratio in Canine Heartworm Disease

Abstract: Background:Dirofilaria immitis produces proliferative pulmonary endarteritis and pulmonary thromboembolism in infected dogs. The pulmonary vascular lesions lead to irreversible and persistent structural damage and, as a consequence, sustained precapillary pulmonary hypertension (PH). The purpose of this study was to assess the diagnostic value of the pulmonary vein to pulmonary artery ratio (PV:PA ratio) to determine moderate or severe PH (>50 mmHg) in dogs with heartworm disease. Methods: A total of 151 na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…The employment of RPADi has been ratified by numerous studies as a useful method to help in the detection of PH in dogs infected with D. immitis . In this study, PH was identified in 41% of dogs with heartworm, and in all cases, RPADi was <30% [ 23 , 24 , 28 , 30 ]. Additionally, previous studies have demonstrated statistically significant differences in dogs with PH compared to those without, regardless of whether they were healthy or infected with D. immitis [ 1 , 2 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…The employment of RPADi has been ratified by numerous studies as a useful method to help in the detection of PH in dogs infected with D. immitis . In this study, PH was identified in 41% of dogs with heartworm, and in all cases, RPADi was <30% [ 23 , 24 , 28 , 30 ]. Additionally, previous studies have demonstrated statistically significant differences in dogs with PH compared to those without, regardless of whether they were healthy or infected with D. immitis [ 1 , 2 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 72%
“…This produces an increase in right ventricular afterload, which leads to a decrease in ventricular contraction (strain). PH is common in dogs with heartworm disease (although it is often not present), occurring in 30–67% of infected dogs (41% in the current study) [ 2 , 23 , 24 , 28 ]. When severe, PH can lead to R-CHF [ 2 , 28 ].…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations